2013
DOI: 10.2460/ajvr.74.5.744
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of total white blood cell count as a marker for proviral load of bovine leukemia virus in dairy cattle from herds with a high seroprevalence of antibodies against bovine leukemia virus

Abstract: These data have provided an updated reference interval for WBC counts in Holstein cows from herds with high BLV seroprevalence. In dairy cattle under natural conditions, WBC count was correlated with bPVL; thus, WBC count determination could be a potential tool for monitoring BLV infection levels in attempts to control transmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 16 publications
3
35
1
3
Order By: Relevance
“…WBC count reference intervals (i.e., mean ± 2 SD) for BLV-negative and BLV-positive groups have been ranged from 5,906 to 16,609 WBCs/µL and from 4,710 to 29,322 WBCs/µL, respectively ( Table 2). Our results are consistent with the data of other authors, wherein the correlation of total WBC counts and BLV proviral loads in BLV-infected animals has been investigated [45,46]. It is despite the fact, that apart from BLV infection, the increase of the number of WBCs can be the consequence of inflammation, stress, injury, leukemia, and other infections [47].…”
Section: Discussionsupporting
confidence: 93%
“…WBC count reference intervals (i.e., mean ± 2 SD) for BLV-negative and BLV-positive groups have been ranged from 5,906 to 16,609 WBCs/µL and from 4,710 to 29,322 WBCs/µL, respectively ( Table 2). Our results are consistent with the data of other authors, wherein the correlation of total WBC counts and BLV proviral loads in BLV-infected animals has been investigated [45,46]. It is despite the fact, that apart from BLV infection, the increase of the number of WBCs can be the consequence of inflammation, stress, injury, leukemia, and other infections [47].…”
Section: Discussionsupporting
confidence: 93%
“…Animals with an increase in white cell count of three standard deviations above the median and with similar counts for a period of not less than two months can be considered to have PL [21]. Over the last decade, major studies involving infected animals have allowed a more thorough classification [2,11,15,16]. Within the PL group, all animals carry a high proviral load and develop a strong immune response against the major antigenic proteins of the viral particle, p24 and gp51, and these are called the high proviral load (HPL) group.…”
Section: Introductionmentioning
confidence: 99%
“…Real-time PCR and ELISA are widely used in Japan to identify BLV-infected dairy cattle (Nishiike et al, 2016). The test and segregate or test and manage strategy has been practiced in Argentina as well (Gutiérrez et al, 2011(Gutiérrez et al, , 2012Alvarez et al, 2013). Quantitative real-time PCR has been used to determine proviral load (PVL) in Japan (Jimba et al, 2010;Jimba et al, 2012), and BLV-infected cows with PL have been shown to have significantly higher PVL than AL cows (Ohno et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Jimba et al (2012) suggested only partial correlation between PVL per 100,000 peripheral white blood cells measured using real-time PCR and serological results. A hematological approach showed that white blood cell count was correlated with blood PVL and can be a good monitoring tool (Alvarez et al, 2013).…”
Section: Introductionmentioning
confidence: 99%